2007
DOI: 10.1016/j.bone.2006.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic bone assessment: “The time has come”

Abstract: Bone is unique in its ability to maintain its strength in the presence of constant turnover. It has been established that there is gradual and relatively complete removal and replacement with new bone several times in a lifetime. The reparative pattern is constantly changing in order to maintain strength and is influenced by changes in general health, the presence of disease, and the degree of physical activity. To date, no method has been developed to measure the nature of lifetime changes in patterns during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 44 publications
(53 reference statements)
0
34
0
Order By: Relevance
“…Despite this, several studies have demonstrated high levels of correlation between heel trabecular sound transmission and aBMD at matched skeletal sites [48][49][50]. Moreover, both SOS and BUA, standard QUS measurements, are dependent on overall bone strength which, in turn, is related to bone density, architecture and turnover, and the extent of bone mineralization [48,50,[51][52][53][54][55][56]. These factors likely work together to maintain the overall quality and strength of bone and to prevent fractures and other bone failure.…”
Section: Quantitative Ultrasound (Qus) Bone Assessment Methodsmentioning
confidence: 99%
“…Despite this, several studies have demonstrated high levels of correlation between heel trabecular sound transmission and aBMD at matched skeletal sites [48][49][50]. Moreover, both SOS and BUA, standard QUS measurements, are dependent on overall bone strength which, in turn, is related to bone density, architecture and turnover, and the extent of bone mineralization [48,50,[51][52][53][54][55][56]. These factors likely work together to maintain the overall quality and strength of bone and to prevent fractures and other bone failure.…”
Section: Quantitative Ultrasound (Qus) Bone Assessment Methodsmentioning
confidence: 99%
“…In particular, quantitative ultrasound has been considered as an attractive alternative to the use of Dual Energy X-Ray Absorptiometry (DEXA) to diagnose osteoporosis (Siffert and Kaufman, 2006;Hans et al, 1996;Grimm and Williams, 1997a) because it is non-ionizing, inexpensive, and non-invasive. Ultrasound waves are elastic vibrations that can provide direct information on the mechanical properties of the medium in which they propagate.…”
Section: Introductionmentioning
confidence: 99%
“…110,112,[114][115][116][117][118][119][120][121] These factors likely work together to maintain overall bone quality and strength, and to prevent fractures and other bone failure. 110,112,[114][115][116][117][118][119][120][121] QUS parameters related to heel trabecular transverse transmission are highly correlated with bone strength. 117,[122][123][124][125][126][127][128][129] Consequently, it is conceivable that guidelines could be created using QUS to guide when to initiate osteoporosis treatment, Currently, a World Health Organization (WHO) task force is developing a model to predict the 10-year probability of osteoporosis-related fractures, combining femoral neck DXA BMD measurements and CRF.…”
Section: ) Using Qus To Initiate Osteoporosis Treatmentmentioning
confidence: 99%
“…Despite this, several studies have demonstrated high levels of correlation (r ~ 0.90) between heel trabecular sound transmission and BMD at matched skeletal sites. [110][111][112][113] Moreover, both SOS and BUA, standard QUS measurements, are dependent upon overall bone strength which, in turn, is related to bone density, architecture and turnover, and the extent of bone mineralization. 110,112,[114][115][116][117][118][119][120][121] These factors likely work together to maintain overall bone quality and strength, and to prevent fractures and other bone failure.…”
Section: ) Using Qus To Initiate Osteoporosis Treatmentmentioning
confidence: 99%
See 1 more Smart Citation